On criminogenic grit and theoretical criminology - Okeem, Chidike I. (Journal of Theoretical and Philosophical Criminology, 2020)
Given the interdisciplinary nature of criminology, this paper presents the perspective that the continued attention to trends in other social science disciplines is necessary for the theoretical advancement of the field. The paper presents the idea of criminogenic grit being a useful theoretical perspective that can help to improve some of the most popular criminological theories. The paper begins with a review of the extant literature on psychological grit, suggests theoretical improvements to the concept of grit, and discusses some of the specific ways in which psychological grit can be related to contemporary theoretical criminology.